Benthic primary producers are key to sustain the Wadden Sea food web: stable carbon isotope analysis at landscape scale. Issue 6 (30th May 2017) - Christianen, M. J. A.; Middelburg, J. J.; Holthuijsen, S. J.; Jouta, J.; Compton, T. J.; van der Heide, T.; Piersma, T.; Sinninghe Damsté, J. S.; van der Veer, H. W.; Schouten, S.; Olff, H.
Abstract: Coastal food webs can be supported by local benthic or pelagic primary producers and by the import of organic matter. Distinguishing between these energy sources is essential for our understanding of ecosystem functioning. However, the relative contribution of these components to the food web at the landscape scale is often unclear, as many studies lack good taxonomic and spatial resolution across large areas. Here, using stable carbon isotopes, we report on the primary carbon sources for consumers and their spatial variability across one of the world's largest intertidal ecosystems (Dutch Wadden Sea; 1460 km 2 intertidal surface area), at an exceptionally high taxonomic (178 species) and spatial resolution (9, 165 samples from 839 locations). The absence of overlap in δ 13 C values between consumers and terrestrial organic matter suggests that benthic and pelagic producers dominate carbon input into this food web. In combination with the consistent enrichment of benthic primary producers (δ 13 C −16.3‰) relative to pelagic primary producers (δ 13 C −18.8) across the landscape, this allowed the use of a two‐food‐source isotope‐mixing model. This spatially resolved modelling revealed that benthic primary producers (microphytobenthos) are the most important energy source for the majority of consumers at higher trophic levels (worms, molluscs, crustaceans, fish, and birds), and thus to the whole food web. In addition, we found large spatial heterogeneity in the δ 13 C values of benthic primary producers (δ 13 C −19.2 to −11.5‰) and primary consumers (δ 13 C −25.5 to −9.9‰), emphasizing the need for spatially explicit sampling of benthic and pelagic primary producers in coastal ecosystems. Our findings have important implications for our understanding of the functioning of ecological networks and for the management of coastal ecosystems.